Infrared thermography for the evaluation of adolescent and juvenile idiopathic scoliosis: A systematic review. (April 2023) - Roggio, Federico; Petrigna, Luca; Filetti, Veronica; Vitale, Ermanno; Rapisarda, Venerando; Musumeci, Giuseppe
Abstract: Introduction: Adolescent and Juvenile Idiopathic Scoliosis are a three-dimensional spine deformity characterized by a muscle alteration of the convex and concave sides of the scoliosis, which can be evaluated with different non-invasive and radiation-free methods such as infrared thermography. The objective of the present review is to assess infrared thermography as a potential method to evaluate alterations of the scoliosis. Materials and methods: A systematic review was performed by collecting articles from PubMed, Web of Science, Scopus, and Google Scholar, published from 1990 to April 2022, on the use of infrared thermography to evaluate adolescent and juvenile idiopathic scoliosis. Relevant data were collected in tables, and the primary outcomes were discussed narratively. Results: Of the 587 articles selected, only 5 were in line with the objective of this systematic review and were eligible for the inclusion criteria. The findings of the selected articles corroborate the applicability of infrared thermography as an objective method to assess the thermal differences of the muscles between the convex and concave sides of scoliosis. The overall quality of the research was uneven in the reference standard method and assessment of measures. Conclusion: Infrared thermography is providing promising results to discriminate thermal differences in scoliosis evaluation, albeit there are still some concerns about considering it as a diagnostic tool for scoliosis evaluation because specific recommendations for collecting data are not met. We propose additional recommendations to existing guidelines to perform thermal acquisition to reduce errors and provide the best results to the scientific community. Highlights: Infrared thermography is a valid method to assess scoliosis alterations. The muscles of scoliosis convex and concave sides are thermally different. The mean temperature difference of upper back in scoliotic individuals is 0.3°. We propose a standard procedure to follow when assessing scoliosis with IRT.